1997
DOI: 10.1007/bf02385274
|View full text |Cite
|
Sign up to set email alerts
|

The role of polyamines in liver regeneration after hepatectomy with ischemic injury

Abstract: A total of 175 rats were divided into: (1) a sham operation group, in which the liver was slightly mobilized after laparotomy; (2) a control group in which 68% of the liver was resected without the blockade of blood flow; (3) an ischemia + hepatectomy group, in which the vessels entering the right and caudate lobes were clamped for 30 min, and the nonischemic lobes were resected; (4) a DFMO + ischemia + hepatectomy group, in which the same procedure as for the ischemia + hepatectomy group was performed, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…These results implied that the peak level of SPD beyond the baseline level might be needed to obtain significant effects of polyamines on IRI and regeneration. This finding is supported by other publications reporting that bolus administration of polyamines significantly attenuates injury or promotes regeneration [6, 7, 9, 10]. Additionally, it is also supported by pharmacokinetics/pharmacodynamics theory in pharmacy, which describes the time course of effect intensity in response to administration of an antibiotics dose [17].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…These results implied that the peak level of SPD beyond the baseline level might be needed to obtain significant effects of polyamines on IRI and regeneration. This finding is supported by other publications reporting that bolus administration of polyamines significantly attenuates injury or promotes regeneration [6, 7, 9, 10]. Additionally, it is also supported by pharmacokinetics/pharmacodynamics theory in pharmacy, which describes the time course of effect intensity in response to administration of an antibiotics dose [17].…”
Section: Discussionsupporting
confidence: 67%
“…Previous reports demonstrated that polyamines ameliorate ischemia-reperfusion injury (IRI) and promote regeneration [5-7]. We also reported that oral polyamine administration by gastric tube alleviates IRI and promotes regeneration in inbred rats [8].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…21) ODC is known to be involved in cell growth in regenerating liver after partial hepatectomy. [10][11][12] The relationship between TGase and ODC activity must be observed in regenerating liver, since polyamines which are ODC-catalyzed products are good substrates of TGase. Therefore, DNA synthesis in the differential growth capacities between PPH and PVH of regenerating liver may be reciprocally regulated by TGase and ODC.…”
Section: Discussionmentioning
confidence: 99%
“…8) Also, ornithine decarboxylase (ODC; EC 4.1.1.7) is known to be involved in cell growth and its activity increases rapidly and markedly in regenerating liver after partial hepatectomy. [10][11][12] Moreover, endogenous aliphatic polyamines, putrescine (PUT), spermidine (SPD) and spermine (SPM) are produced consequently by ODC from ornithine. PUT, SPD and SPM are also physiological substrates for TGase.…”
mentioning
confidence: 99%